M2-AChR Mediates Rapid Antidepressant Effects of Scopolamine Through Activating the mTORC1-BDNF Signaling Pathway in the Medial Prefrontal Cortex - Liu, Shuang; Shi, Dandan; Sun, Zuoli; He, Yi; Yang, Jian; Wang, Gang (Frontiers in Psychiatry, 2021)
Background: Scopolamine, a nonselective muscarinic acetylcholine receptor (M1~5-AChR) antagonist, has rapid and robust antidepressant effects in humans and other species. Which of the five M-AChRs mediates these therapeutic effects has not been fully identified. Several studies implicate M2-AChR as a potential antidepressant target of scopolamine. This study aimed to explore the role of M2-AChR in scopolamine’s antidepressant effects, and determine the underlying mechanisms. Methods: We used the classic novelty suppressed feeding test (NSFT), open field test (OFT) and forced swim test (FST) to observe antidepressant-related behaviors of normal rats, medial prefrontal cortex (mPFC) neuron silenced rats and M2-AChR knockdown rats treated with scopolamine. The M2 cholinergic receptor antagonist methoctramine (MCT) was injected into normal rats as a further experiment. Levels of mTORC1 and brain-derived neurotrophic factor (BDNF) in the mPFC of animals were analyzed by Western blotting. Results: mPFC is required for the antidepressant effects of scopolamine, which were blocked after silencing of neurons in the mPFC. Similar results could be observed after injecting rats with MCT. Using AAV-CHRM2 (adeno-associated virus-CHRM2) to knock down M2-AChR in the mPFC resulted in the antidepressant effects of scopolamine being blunted. Furthermore, Western blotting demonstrated increased expression of mTORC1 signaling and BDNF in MCT-treated rats. Conclusion: Our results indicate that M2-AChR in the mPFC mediates the antidepressant effects of scopolamine by inducing release of BDNF and activating the mTORC1 signaling pathway.